Synthesis, and Spectral Characterization of 6-O-Octanoyl-1,2-O-isopropylidene-α-D-glucofuranose Derivatives - Puja DEVİ (Turkish Chemical Society, 2021)
Site selective acylation of monosaccharides and oligosaccharides are very necessary for the preparation of both natural and novel synthetic carbohydrate compounds, synthetic intermediates, postglycosylation modifications, and for the preparation of therapeutic agents including research tools for glycobiology. Hence, site selective octanoylation of 1,2-O-isopropylidene-α-D-glucofuranose was conducted. Under low temperature in anhydrous pyridine direct unimolar octanoylation of this glucofuranose without any catalyst exhibited selectivity at C-6 hydroxyl group. The C-6 O-octanoylglucofuranose, thus obtained, was then used for the preparation of three 3,5-di-O-acyl esters in a similar direct method to get novel esters of glucofuranose. Characterization of all the glucofuranose esters by 1D and 2D spectroscopic technique is also discussed herein.